Long-term, Prolonged-release Tacrolimus-based Immunosuppression in De Novo Liver Transplant Recipients: 5-year Prospective Follow-up of Patients in the DIAMOND Study. Issue 8 (August 2021) - Friman, Styrbjörn; Tisone, Giuseppe; Nevens, Frederik; Lehner, Frank; Santaniello, Walter; Bechstein, Wolf O.; Zhuvarel, Sergey V.; Isoniemi, Helena; Rummo, Oleg O.; Klempnauer, Jürgen; Anaokar, Swapneel; Hurst, Martin; et al.
Abstract : Background: Immunosuppression with calcineurin inhibitors (CNIs) is reportedly associated with risk of renal impairment in liver transplant recipients. It is believed that this can be mitigated by decreasing initial exposure to CNIs or delaying CNI introduction until 3–4 d posttransplantation. The ADVAGRAF studied in combination with mycophenolate mofetil and basiliximab in liver transplantation (DIAMOND) trial evaluated different administration strategies for prolonged-release tacrolimus (PR-T). Methods: DIAMOND was a 24-wk, open-label, phase 3b trial in de novo liver transplant recipients randomized to: PR-T 0.2 mg/kg/d (Arm 1); PR-T 0.15–0.175 mg/kg/d plus basiliximab (Arm 2); or PR-T 0.2 mg/kg/d delayed until day 5 posttransplant plus basiliximab (Arm 3). In a 5-y follow-up, patients were maintained on an immunosuppressive regimen according to standard clinical practice (NCT02057484). Primary endpoint: graft survival (Kaplan-Meier analysis). Results: Follow-up study included 856 patients. Overall graft survival was 84.6% and 73.5% at 1 and 5 y post transplant, respectively. Five-year rates for Arms 1, 2, and 3 were 74.7%, 71.5%, and 74.5%, respectively. At 5 y, death-censored graft survival in the entire cohort was 74.7%. Overall graft survival in patients remaining on PR-T for ≥30 d was 79.1%. Graft survival in patients who remained on PR-T at 5 y was 87.3%. Patient survival was 86.6% at 1 y and 76.3% at 5 y, with survival rates similar in the 3 treatment arms at 5 y. Estimated glomerular filtration rate at the end of the 24-wk initial study and 5 y posttransplant was 62.1 and 61.5 mL/min/1.73 m 2, respectively, and was similar between the 3 treatment arms at 5 y. Overall, 18 (2.9%) patients had ≥1 adverse drug reaction, considered possibly related to PR-T in 6 patients. Conclusions: In the DIAMOND study patient cohort, renal function, graft survival, and patient survival were similar between treatment arms at 5 y posttransplant. Abstract : Supplemental Digital Content is available in the text.